2017
DOI: 10.1159/000453594
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane Mucins: Signaling Receptors at the Intersection of Inflammation and Cancer

Abstract: Mucosal surfaces line our body cavities and provide the interaction surface between commensal and pathogenic microbiota and the host. The barrier function of the mucosal layer is largely maintained by gel-forming mucin proteins that are secreted by goblet cells. In addition, mucosal epithelial cells express cell-bound mucins that have both barrier and signaling functions. The family of transmembrane mucins consists of diverse members that share a few characteristics. The highly glycosylated extracellular mucin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
237
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(239 citation statements)
references
References 153 publications
2
237
0
Order By: Relevance
“…They seem to have evolved to monitor and repair damaged epithelia, whereas this function can be "hijacked" by cancer cells (van Putten & Strijbis, 2017). They seem to have evolved to monitor and repair damaged epithelia, whereas this function can be "hijacked" by cancer cells (van Putten & Strijbis, 2017).…”
mentioning
confidence: 99%
“…They seem to have evolved to monitor and repair damaged epithelia, whereas this function can be "hijacked" by cancer cells (van Putten & Strijbis, 2017). They seem to have evolved to monitor and repair damaged epithelia, whereas this function can be "hijacked" by cancer cells (van Putten & Strijbis, 2017).…”
mentioning
confidence: 99%
“…Lining the apical surface of epithelial cells are one or more members of the family of membrane‐associated mucins (MAMs) consisting of genes MUCs 1 , 3 , 4 , 12 , 13 , 15 , 16 , 17 , 20 , and 21 (Corfield, ; van Putten & Strijbis, ). MAMs are comprised of a cytoplasmic domain, a transmembrane domain, and an extracellular domain containing a highly glycosylated region characteristic of mucins: tandem repeats rich in serines and threonines, coupled to oligosaccharides via specific O‐glycosidic bonds (van Putten & Strijbis, ).…”
Section: Introductionmentioning
confidence: 99%
“…Lining the apical surface of epithelial cells are one or more members of the family of membrane‐associated mucins (MAMs) consisting of genes MUCs 1 , 3 , 4 , 12 , 13 , 15 , 16 , 17 , 20 , and 21 (Corfield, ; van Putten & Strijbis, ). MAMs are comprised of a cytoplasmic domain, a transmembrane domain, and an extracellular domain containing a highly glycosylated region characteristic of mucins: tandem repeats rich in serines and threonines, coupled to oligosaccharides via specific O‐glycosidic bonds (van Putten & Strijbis, ). The extracellular domain of MAMs is posited to aid in hydration and lubrication via hydroscopic acidic oligosaccharides (sulfated and sialylated) (Alliende et al, ), and MAMs have been shown to provide a barrier against adherence of bacteria and viruses, or to be released from the membrane to clear bound microorganisms (Menon et al, ; van Putten & Strijbis, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The airways are the most common port of entry for severe infections. Here, highly specialized epithelial cells and mucins play important roles to keep us healthy [4-6]. However, bacteria can manipulate host defense, thereby creating a niche for survival in an environment that otherwise should be hostile [7-9].…”
mentioning
confidence: 99%